Infrared‐Emitting Multimodal Nanostructures for Controlled In Vivo Magnetic Hyperthermia. Issue 30 (12th June 2021) - Ximendes, Erving; Marin, Riccardo; Shen, Yingli; Ruiz, Diego; Gómez‐Cerezo, Diego; Rodríguez‐Sevilla, Paloma; Lifante, Jose; Viveros‐Méndez, Perla X.; Gámez, Francisco; García‐Soriano, David; Salas, Gorka; Zalbidea, Carmen; et al.
Abstract: Deliberate and local increase of the temperature within solid tumors represents an effective therapeutic approach. Thermal therapies embrace this concept leveraging the capability of some species to convert the absorbed energy into heat. To that end, magnetic hyperthermia (MHT) uses magnetic nanoparticles (MNPs) that can effectively dissipate the energy absorbed under alternating magnetic fields. However, MNPs fail to provide real‐time thermal feedback with the risk of unwanted overheating and impeding on‐the‐fly adjustment of the therapeutic parameters. Localization of MNPs within a tissue in an accurate, rapid, and cost‐effective way represents another challenge for increasing the efficacy of MHT. In this work, MNPs are combined with state‐of‐the‐art infrared luminescent nanothermometers (LNTh; Ag2 S nanoparticles) in a nanocapsule that simultaneously overcomes these limitations. The novel optomagnetic nanocapsule acts as multimodal contrast agents for different imaging techniques (magnetic resonance, photoacoustic and near‐infrared fluorescence imaging, optical and X‐ray computed tomography). Most crucially, these nanocapsules provide accurate (0.2 °C resolution) and real‐time subcutaneous thermal feedback during in vivo MHT, also enabling the attainment of thermal maps of the area of interest. These findings are a milestone on the road toward controlled magnetothermal therapies with minimal side effects. Abstract : Iron oxide and silver sulfide nanoparticles are combined in optomagnetic nanocapsules, which can act as multimodal contrast agents for several imaging modalities (fluorescence imaging, magnetic resonance imaging, computed tomography, optical tomography, and photoacoustic imaging). More importantly, these nanocapsules enable real‐time subcutaneous thermal monitoring of magnetic hyperthermia processes, paving the way to fully controlled magnetic therapies.